717 The role of physical exercise in modifying cardiovascular parameters in hypertensive patients (Balneo and PRM Research Journal, 2024)
Hypertension is among the top risk factors for cardiovascular diseases.  Diversified rehabilitation programs are needed to limit the progression of the high blood pressure condition. The welfare of aquatic therapy is acknowledged, but hydrotherapeutic procedures are rarely used in cardiovascular diseases. The study aims to assess the impact of an exhaustive hydro-kinetic thermo therapeutic program compared to other methods of treatment, i.e., cardiovascular rehabilitation program, recommendation for a healthy life, and antihypertensive medication. Four groups of patients (46 years ±0,32) diagnosed with hypertension participated in four different rehabilitation programs to analyze the impact on their effort capacity. Their ability to achieve average effort without the appearance of fatigue symptoms was studied for a period of eight weeks by monitoring six parameters: systolic blood pressure (SBP), diastolic blood pressure (DBP), Borg Scale, Medical Research Council Dyspnoea Scale (MRC-DS), pulse (P) and oxygen saturation (O2). Group A, which benefited only of recommendations for a healthy life, didn’t register any significant p values between the initial and final evaluation; group B, which had medications and recommendations for a healthy life, registered significant p values for 2 parameters (SBP and P have p